The Diffrences in Student’s Grade Point Average (GPA) Based on SBMPTN of UTBC and UTBK and External Motivation in Choosing PMIPA Majors of Tadulako University - Lumbantobing, Ria; Napitupulu, Mery; Ratman, Ratman (Jurnal Universitas Tadulako, 2023)
This study aims to describe the differences in student's GPAs at the Mathematics and Natural Science Education (PMIPA) Department of Tadulako University who enter through the Joint Selection to Enter State Universities (SBMPTN) pathway with the Print-Based Written Test (UTBC) in 2018 and Computer-Based Writing Examination (UTBK) systems in 2019, describe the relationship of external motivation of students in choosing majors with GPA based on the SBMPTN (UTBC and UTBK) pathway. The samples used were all students at the PMIPA Study Program of Tadulako University who entered through the UTBC SBMPTN pathway in 2018 as many as 134 students and 130 students of UTBK 2019. There is an insignificant difference in the students' GPA through the UTBC and UTBK SBMPTN pathway. The students of UTBK have a higher GPA in the second semester than the students of UTBC, with the average GPA of UTBC students is 3.407, and the average GPA of UTBK students is 3.525. There is no relationship between students' external motivation in choosing a major against students' GPA at the PMIPA department of Tadulako University, but factors of interest and self-will influence it.